A systematic review and meta-analysis of the effects of temperature on the development and survival of the Aedes mosquito - Nik Abdull Halim, Nik Muhammad Hanif; Che Dom, Nazri; Dapari, Rahmat; Salim, Hasber; Precha, Nopadol (Frontiers Media, 2022)
Introduction: The Aedes mosquito species, which are the vectors for the transmission of the dengue virus (DENV) to humans, are becoming increasingly susceptible to the formidable effects of influential factors, especially temperature. However, there are still very few studies that have systematically reviewed the existing literature. Hence, in the present study, a systematic literature review and meta-analysis was conducted into the effects of temperature on dengue vectors. Method: Several research methodologies were incorporated into the current study, and a review was carried out using PRISMA as a guide. The publications for this study were chosen from two prominent databases, Scopus and Web of Science. All of the studies were assessed, reviewed, and evaluated independently by two reviewers. The meta-analysis tool, Review Manager (RevMan Copenhagen Version 5.4.1), was used to record the extracted data for the meta-analysis. Moran's I2 and a funnel plot were utilized to measure heterogeneity, and publication bias was investigated. A 95% confidence interval (CI) and overall risk difference (RD) were estimated using a random-effects model. Result and discussion: As a consequence of the search efforts, a total of 46 articles were selected for inclusion in the systematic review and meta-analysis. This review was divided into five major themes, based on a thematic analysis: (i) hatching rate, (ii) development time, (iii) longevity, (iv) survival rate, and (v) wing morphology. In addition, the development time, survival rate, and wing morphology revealed significantly higher risk differences between the maximum and minimum temperatures (RD: 0.26, 95% CI: 0.16, 0.36; p = < 0.00001; RD: 0.10, 95% CI: 0.05, 0.14; p < 0.0001; and RD: 0.07, 95% CI: 0.02, 0.12; p = 0.006, respectively). This study makes several substantial contributions to the body of knowledge and to practical applications. Finally, a number of recommendations are made at the conclusion of this research for the future reference of researchers.